Nutrition, Microbiota and Noncommunicable Diseases - Plaza-Díaz, Julio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Health is defined as "the state of the organism when it functions optimally without evidence of disease". Surprisingly, the words "microbes" or "microorganism" are missing in this definition. The regulation of gut microbiota is mediated by an enormous quantity of aspects, such as microbiological factors, host characteristics, diet patterns, and environmental variables. Some protective, structural, and metabolic functions have been reported for gut microbiota, and these functions are related to the regulation of homeostasis and host health. Host defense against pathogens is, in part, mediated through gut microbiota action and requires intimate interpretation of the current microenvironment and discrimination between commensal and occasional bacteria. The present Special Issue provides a summary of the progress on the topic of intestinal microbiota and its important role in human health in different populations. This Special Issue will be of great interest from a clinical and public health perspective. Nevertheless, more studies with more samples and comparable methods are necessary to understand the actual function of intestinal microbiota in disease development and health maintenance.